Analysis of Microbial Community, Volatile Flavor Compounds, and Flavor of Cigar Tobacco Leaves From Different Regions - Zheng, Tianfei; Zhang, Qianying; Li, Pinhe; Wu, Xinying; Liu, Yi; Yang, Zhen; Li, Dongliang; Zhang, Juan; Du, Guocheng (Frontiers in Microbiology, 2022)
Although the international trade of cigar tobacco leaves (CTLs) is booming, the main characteristics of tobacco leaves from different producing areas are rarely reported. This study aimed to characterize the microbial community, volatile flavor compounds (VFCs) and flavor of CTLs from four famous cigar producing areas, including Dominica, Brazil, Indonesia, and China. High-throughput sequencing results showed that the dominant genera in CTLs were Staphylococcus, Pseudomonas, Aspergillus, Sampaiozyma, and Alternaria. Sensory analysis revealed that Indonesian and Chinese CTLs were characterized considerably by leathery, peppery, and baked aroma. Brazilian CTLs were dominated by caramel and herb aroma. Dominican CTLs had aromas of milk, fruity, sour, cream, flower, nutty, and honey. Supplemented with the determination of volatile flavor compounds (VFCs), the flavor of CTLs could be scientifically quantified. The microbial communities, VFCs, and flavors of tobacco leaves vary widely due to geographic differences. Furthermore, network analysis revealed the close relationship between microbes with VFCs and flavors. This study obtained essential information on CTLs, which may be useful for people concerned about tobacco.